Theoretical Simulation of Extended Mid-Wave Infrared High Operating Temperature InSb pBn Photodetectors - Zhang, Yinlin; Li, Chuang; Guo, Daqian; Cheng, Keming; Shen, Kai; Wu, Jiang (IEEE journal of quantum electronics)
The application of the barrier architecture exhibits the potential in reducing the noise current and improving the performance of photodetectors. However, the development of mid-infrared InSb barrier detector is lagging far behind its III-V counterparts due to the problem of lattice mismatch. In this paper, we proposed two InSb barrier detectors that have reduced dark current and raised operating temperatures with the help of commercial software APSYS platform. The incorporation of a In0.72 Al0.28Sb barrier architecture to the InSb absorber offers a significant dark current reduction over the conventional InSb photodiode, regardless the presence of strain-induced defects within the barrier layers. At 150 K, the InSb bulk barrier detector has a cutoff wavelength at 5.65 μ \text{m} . With a barrier design, the dark current, 9.96× 10^{-3}\text{A} /cm2 at −220 mV, is about 77 times lower than the InSb photodiode and the specific detectivity is about 2.07× 10 ^{11} cm Hz ^{1/2} /W with a-220 mV bias voltage, which brings approximately an order of magnitude of performance improvement.